1976
DOI: 10.2307/3428614
|View full text |Cite
|
Sign up to set email alerts
|

Occupational and Environmental Health Hazards in the Plastics Industry

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.. The National Institute of Environmental Health Sciences (NIEHS) andBrogan & Partners are collaborating with JSTOR to digitize, preserve and extend access to Environmental Heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1995
1995
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 1 publication
(1 reference statement)
0
4
0
Order By: Relevance
“…A number of studies have shown that the principal hazards of plastics are associated with their monomers and with the wide variety of additives that are used in processing [Echardt, 1976;Karstadt, 1976;Withey, 19791 Various studies have investigated the effects of exposure, mostly in association with angiosarcoma of the liver in PVC production, in which PVC resins are manufactured from vinyl chloride monomer [Simonato et al, 1991;Wong et al, 1991;Laplanche et al, 19921. Of those investigations, none reported an excess of pancreatic cancer.…”
Section: Discussionmentioning
confidence: 98%
“…A number of studies have shown that the principal hazards of plastics are associated with their monomers and with the wide variety of additives that are used in processing [Echardt, 1976;Karstadt, 1976;Withey, 19791 Various studies have investigated the effects of exposure, mostly in association with angiosarcoma of the liver in PVC production, in which PVC resins are manufactured from vinyl chloride monomer [Simonato et al, 1991;Wong et al, 1991;Laplanche et al, 19921. Of those investigations, none reported an excess of pancreatic cancer.…”
Section: Discussionmentioning
confidence: 98%
“…12,13 It was earlier considered as one of non-toxic material and used general anaesthesia as well. 14 The first report of PVC toxic effects resulting in liver angiosarcoma and acroosteolysis enforced to investigate its similar effects in other neoplastic entities. 15 The inhaled PVC dust component of less than 5µm may travel to respiratory bronchiole and lodge inside the alveoli.…”
Section: Discussionmentioning
confidence: 99%
“…The extent of these hazards varies depending on the industry type, locality and precautionary measures taken by the worker and the employer [107][108][109]. The extent of chemical hazards, for example, occurs due to unreacted feedstocks and other process inputs, such as fillers, stabilisers, pigments, inhibitors and initiators, all added to a finished product [110]. To compound the problem, there are in excess of 100,000 hazardous chemicals in various workplaces, with new chemicals introduced yearly, all affecting workers [111].…”
Section: Occupational Health Hazards Exposure and Latencymentioning
confidence: 99%